1994
DOI: 10.1172/jci117146
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell degranulation induced by type 1 fimbriated Escherichia coli in mice.

Abstract: The strategic location of mast cells at the host-environment interface and their ability to release potent mediators of inflammation have suggested that these cells may play a pivotal role in host defense against bacterial infection. The ability of the opportunistic pathogen, Escherichia coli, to induce degranulation of mast cells obtained from the mouse peritoneum was investigated. We determined that unlike a mutant derivative deficient in the FimH subunit of the fimbriae or nonfimbriated E. coli, type 1 fimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 34 publications
4
81
0
Order By: Relevance
“…Labeling of TNP-PSGs with Alexa Fluor 488 or Alexa Fluor 633 was performed using Alexa Fluor 488 or Alexa Fluor 633 carboxylic acid succinimidyl ester, respectively. The E. coli strain used for these studies was ORN103(pUT2002), a nonadherent, fimbriated K-12 laboratory strain (21). TNP-E. coli was generated as described for TNP-PSG.…”
Section: Modification Of Psg and Escherichia Colimentioning
confidence: 99%
See 2 more Smart Citations
“…Labeling of TNP-PSGs with Alexa Fluor 488 or Alexa Fluor 633 was performed using Alexa Fluor 488 or Alexa Fluor 633 carboxylic acid succinimidyl ester, respectively. The E. coli strain used for these studies was ORN103(pUT2002), a nonadherent, fimbriated K-12 laboratory strain (21). TNP-E. coli was generated as described for TNP-PSG.…”
Section: Modification Of Psg and Escherichia Colimentioning
confidence: 99%
“…Because Ags found on common particulate allergens have not been characterized and the specific IgE Abs to these Ags are not readily available, we initiated our studies by generating a particulate allergen through the covalent binding of TNP moieties to an inert laboratory E. coli strain, ORN103(pUT2002) (21). TNP is routinely used as an Ag for in vitro assays because of the commercial availability of specific IgE Abs.…”
Section: Phagocytosis Of Particulate Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the involvement of these cells in defense against microorganisms has been demonstrated only in the last few years [4]. MC constitute a unique link between innate and acquired immunity because they express, on one hand, receptors for complement products [5] and bacterial and parasitic components [6,7] and, on the other hand, they express MHC class I molecules and Ig receptors, including high-affinity IgE receptors and different subtypes of IgG receptors. It is well known that the engagement of high-affinity IgE receptors or of certain types of IgG receptors on MC induces a cascade of events leading to MC activation and, as a consequence, to partial or complete release of stored and/or neosynthesized mediators including mediators of inflammation (histamine, proteoglycans, lipids), cytokines [interleukin (IL)-1, IL-3, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13, tumor necrosis factor ␣ (TNF-␣), platelet-derived growth factor (PDGF), granulocyte-macrophage colony-stimulating factor (GM-CSF)] and chemokines [IL-8, monocyte chemotactic protein 1 (MCP-1), macrophage inflammatory protein-1␣ (MIP-1␣), MIP-1␤] [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of serum opsonins, this interaction resulted in loss of bacterial viability [3] followed by processing of bacterial antigens and eventual presentation of specific bacterial antigens to T cells [4]. These mast cell responses together with their intrinsic capacity to release a range of proinflammatory mediators on contact with bacteria or bacterial products [5] indicated that these cells play a critical role in host defense against infectious agents. That mast cells were indeed pivotal in host defense was recently demonstrated in in vivo studies where mast cell-deficient mice but not their congenic mast cell-sufficient counterparts were found to be highly susceptible to lethal bacterial infections [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%